Hubungan Emotional Regulation dengan Kejadian Bullying pada Remaja - Ardiansyah, Anggriyan Benny; Sholikhah, Siti; Susanti, Inta (Lontara Journal of Health Science and Technology, 2026)
The phenomenon of bullying in the school environment is still a serious problem that has a negative impact on the psychological development of adolescents. Emotional regulation plays an important role in controlling aggressive behavior that can trigger bullying. This study aims to determine the relationship between emotional regulation and bullying incidents in adolescents. The research design used a correlational analytical method with a cross-sectional approach. A sample of 90 grade VII students was taken using a total sampling technique. Data collection was carried out using a closed questionnaire, and data analysis used the Spearman Rho test. The results showed that most respondents had a high level of emotional regulation (70%) and a low incidence of bullying (56.7%). There was a significant relationship between emotional regulation and bullying incidents with a p value = 0.016 and a correlation coefficient value of rₛ = -0.253 which indicated a negative relationship direction and sufficient correlation strength. This means that the better the adolescent's emotional regulation ability, the lower the level of involvement in bullying. This finding strengthens the importance of developing emotional regulation skills as a preventive measure against bullying behavior in schools. Further research is recommended to add other external variables such as family or peer influence.